Effect of Hearing Status on modified Balance Error Scoring System Performance Authors - Matthew Brancaleone; Claire Akard; Jaclyn Caccese (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association)
OBJECTIVE Concussion assessments typically include evaluations of self-reported symptoms, neurocognitive function, and postural control. Specifically, postural control is often assessed using the modified Balance Error Scoring System (mBESS). Although normative mBESS data exist, they may not be appropriate for all athletes, such as those who are deaf or hard-of-hearing (D/HoH). Given the relationship between the cochlea and the vestibular system, athletes who are D/HoH may exhibit differences in postural control due to potential vestibular dysfunction. Therefore, the objective of this study was to compare mBESS performance between athletes who are D/HoH and athletes who are hearing.